Fair, square & legal : safe hiring, managing & firing practices to keep you & your company out of court - Weiss, Donald H., 1936- (AMACOM, American Management Association, 2000)
This updated book shows managers how to protect themselves and their companies from legal problems, and treat their employees fairly. It covers a broad range of employer-employee concerns, from hiring to on-the-job relations, to termination. -- Provided by publisher